Genome-wide and molecular characterization of the DNA replication helicase 2 (DNA2) gene family in rice under drought and salt stress - Saleem, Bilal; Farooq, Umer; Rehman, Obaid Ur; Aqeel, Muhammad; Farooq, Muhammad Shahbaz; Naeem, Muhammad Kashif; Inam, Safeena; Ajmal, Wajya; Rahim, Amna Abdul; Chen, Ming; Kalsoom, Rabia; Uzair, Muhammad; et al. (Frontiers in Genetics, 2022)
Rice plants experience various biotic and abiotic stresses during the growing season, resulting in DNA damage and the subsequent losses in rice production. DNA Replication Helicase/Nuclease2 (DNA2) is known to be involved in DNA replication and repair. The functional mechanisms of the DNA2 gene family in animals and yeast are well documented; however, in crop plants, they remain uninvestigated. To fill this research gap, the current study focused on the genome-wide identification and characterization of OsDNA2 genes, along with analyses of their transcriptional expression, duplication, and phylogeny in rice. Overall, 17 OsDNA2 members were reported to be found on eight different chromosomes (2, 3, 4, 6, 7, 9, 10, and 11). Among these chromosomes (Chr), Chr4 contained a maximum of six OsDNA2 genes. Based on phylogenetic analysis, the OsDNA2 gene members were clustered into three different groups. Furthermore, the conserved domains, gene structures, and cis-regulatory elements were systematically investigated. Gene duplication analysis revealed that OsDNA2_2 had an evolutionary relationship with OsDNA2_14. In addition, to understand the post-transcriptional modification of OsDNA2 genes, miRNAs were predicted, where 653 miRNAs were reported to target 17 OsDNA2 genes. The results indicated that at the maximum, OsDNA2_1 and OsDNA2_4 were targeted by 74 miRNAs each, and OsDNA2_9 was less targeted (20 miRNAs). The three-dimensional (3D) structures of 17 OsDNA2 proteins were also predicted. Expression of OsDNA2 members was also carried out under drought and salt stresses, and their induction indicated the possible involvement of OsDNA2 in DNA repair under stress when compared with the control. Further studies are recommended to confirm where this study will offer valuable basic data on the functioning of DNA2 genes in rice.